Porre, comporre, disporre. Dai giudizi tetici agli enunciati tetici, ai temi e ai loro correlati - Savina Raynaud (Echo des Etudes Romanes, 2012)
The aim of this paper is to identify the theoretical and terminological genesis of one of the two basic notions of Functional Sentence Perspective (FSP), namely that of theme, or basis, of the sentence. Its origin is found in Mathesius’ 1911 article on ellipsis. The choice of such a topic permits a logico-psychological elaboration of speech units inasmuch as ellipsis is taken into consideration as consisting of a missing word, quod non dictum tamen cogitatur. The choice of one-member sentences, especially those without a verb, is convenient from two different perspectives: it recognizes non-standard structures, if compared to the ideal type of the subject – predicate double articulation, and it considers them to be par excellence representatives of the non- synthetic, but rather thetic function of judgements and sentences. The term “one-member thetic sentences” derives from the theory of judgement Mathesius learned from Marty’s philosophy of language. This in turn was fashioned according to Brentano’s classification of psychic phenomena. It is thus possible to reconstruct a fine dissemination of philosophical middle-European thought in linguistic research at the beginning of the Twentieth Century in Bohemia, which is significantly earlier than previously attested to in the literature. Moreover, not only are the syntactic roots of FSP put in evidence, but also the logico-semantic and semantic-communicative ones , a well-established Prague tradition, long before the Circle’s foundation.